1987
DOI: 10.1111/j.2042-7158.1987.tb03405.x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of monoamine oxidase by tricyclic antidepressants: the influence of the nature of the substrate and the source of the enzyme

Abstract: Five tricyclic antidepressants, amitriptyline, clomipramine, desipramine, imipramine and iprindole, have comparable potencies as inhibitors of monoamine oxidase in rodent brain and liver. With rodent brain, potency was always greater with phenethylamine as substrate than with benzylamine, and was generally least with 5-HT. With mouse liver, in which monoamine oxidase is mainly B type, potency with tyramine and dopamine as substrates was close to that found with phenethylamine. The kinetics of inhibition varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that tricyclic antidepressants, such as imipramine, have an inhibitory activity towards MAO and particularly MAO-B (Green & McGachy 1987). However, systematic studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that tricyclic antidepressants, such as imipramine, have an inhibitory activity towards MAO and particularly MAO-B (Green & McGachy 1987). However, systematic studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming this is also true in mice for these antidepressants of broadly similar structure, the expected maximum brain levels from a dose of 20 mg kg-' would be around 60 p~. At such concentrations in-vitro these compounds would be expected to produce around 30% inhibition of 5-HT oxidation but around 70% or more inhibition of PEA oxidation (Green & McGachy 1987).…”
Section: Resultsmentioning
confidence: 94%
“…After 24 h the mice were killed and their brains were homogenized in 0.1 M sodium phosphate buffer (pH 7.4). M A 0 was assayed using [I4C]5-HT (1 1.5 p~) or ['4C]2-phenethylamine (PEA) ( 5 p~) as substrates as described by Green & McGachy (1987). Each assay mixture (total volume 2 mL) contained 5 mg brain tissue when 5hydroxytryptamine (5-HT) was used, but only 0.5 mg when phenethylamine was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo inhibition of the human platelet MAO-B in the patients taking tricyclic antidepressants was not confirmed by others [190][191]. Five tricyclic antidepressants, amitriptyline, clomipramine, desipramine, imipramine and iprindole, have comparable potencies as inhibitors of MAO in rodent brain and liver [192]. These antidepressants have been shown to partially protect mouse brain MAO in vivo from the irreversible enzyme inhibition produced by subsequent injection of phenelzine [193].…”
Section: Inhibition Of Maomentioning
confidence: 97%